PENGARUH PROGRAM KARTU TANI TERHADAP PENURUNAN BIAYA PUPUK PADA PETANI PADI - Mahendra, Bayu; Suprapto, Suprapto; Barima, Hima (Jurnal AGRISEP, 2021)
Fertilizer costs that must be borne by farmers are getting higher and higher and burdensome to farmers. Kartu Tani (Farm Card) is a government program as a form of protection for farmers.Based On 17 paragraph 2 of the Regulation of the Minister of Agriculture (Permentan) No. 10 of 2020. The purpose of this research is to find out how much influence the use of Kartu Tani has on reducing fertilizer costs for farmers. This research uses farmer respondents, with a total of 27 farmers based on consideration of the area of land cultivated and the similarity of commodities. Quantitative descriptive method was used by researchers in this study, so that it can describe the farming business carried out by farmers and the total costs incurred by farmers for the purchase of chemical fertilizers. The results of the descriptive analysis show a decrease in the average cost of fertilizer by IDR 1,316,296 from the cost of IDR 2,032,592 to IDR 716,296. The results of the t-test show the comparison that the costs incurred by farmers before the Kartu Tani program and after the Kartu Tani program are significant, this can be seen from the value of Sig. 0.045 or <0.05, then from the T test results it can be said that the decrease in fertilizer costs is significant. The results of Wilcoxon's analysis showed that all respondents experienced a decrease in fertilizer costs, this was seen from the results of Negative Ranks, which were 27 of a total of 27 respondents.